Formulation of a composite of date palm wood-cement - Touloum, Farid; Younsi, Akli; Kaci, Abdelhak; Benchabane, Adel (Journal of Applied Engineering Science & Technology, 2016)
This work reports the results of an experimental study on the incorporation of wood waste date palm reduced in particles for the manufacture of wood – cement composites. These materials are chipper than the conventional insulator material and environmental friendly. Five types of wood – cement composites with various concentrations of the wood particles, ie. 2, 4, 6, 8 and 10% of total volume, were made according to defined protocol and mix design. Their thermal and mechanical properties were measured and compared to other conventional materials. The obtained results show that the thermal conductivity is positively correlated to the content of particles in the mixture. The compressive strength of composites decreases where the content of particles increase. However, taking account of the ASTM C 109 / C109-95 standard, the wood – cement composite contained 10% of wood particles, considered as lightweight concrete, could be used as non-structural material in construction.
Keywords: Date palm wood; Phoenix Dactylifera (L); Insulator material; Wood-cement composite